2021
DOI: 10.3906/sag-2011-145
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to predicting shoulder dystocia: fetal clavicle measurement

Abstract: Background/aim: This study aimed to evaluate the relationship between second-and third-trimester clavicle lengths and birth weight and shoulder dystocia. Materials and methods:This prospective observational study included 181 patients who presented to the Private Etlik Lokman Hekim Hospital for routine pregnancy visits between March 2019 and March 2020. In addition to routine pregnancy examinations, the patients also underwent ultrasonography twice at weeks 20-23 and 33-36 to determine the length of the fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(42 reference statements)
0
4
0
1
Order By: Relevance
“…Youssef et al evidenced the association between a new ultrasound formula (to measure the fetal biacromial diameter), fetal macrosomia and ShD, which was the starting point of our trial [27]. Similarly, Terzi et al evaluated the role of fetal clavicle length to predict ShD [44]. Their study showed a comparable diagnostic accuracy relative to BA.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Youssef et al evidenced the association between a new ultrasound formula (to measure the fetal biacromial diameter), fetal macrosomia and ShD, which was the starting point of our trial [27]. Similarly, Terzi et al evaluated the role of fetal clavicle length to predict ShD [44]. Their study showed a comparable diagnostic accuracy relative to BA.…”
Section: Discussionmentioning
confidence: 84%
“…Their study showed a comparable diagnostic accuracy relative to BA. However, their study was also limited by a reduced sample size [44]. In our study, the four women who experienced ShD were heterogenous, with two of them with a diagnosis of gestational diabetes mellitus.…”
Section: Discussionmentioning
confidence: 87%
“…The dissection of the symphysis pubis and rupture of the uterus are less commonly recorded. The incidence of the above complications does not appear to be affected by the number or type of manipulations applied to treat shoulder dystocia, except for symphysis pubis dissection and transient uterine neuralgia associated with the McRoberts manipulation mentioned below [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Effectsmentioning
confidence: 99%
“…Las mediciones de extremidades fetales, como la longitud del fémur (LF), permiten evaluar el crecimiento anormal y anomalías esqueléticas (6). Además, existen nomogramas de otras estructuras, como diámetro transverso del cerebelo fetal, clavícula, mandíbula, escápula, arco vertebral, hueso iliaco y pie, que también pueden utilizarse para establecer la velocidad de crecimiento fetal y calcular de la EG (7)(8)(9)(10).…”
Section: Introductionunclassified